2021
DOI: 10.3390/dj9030028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health-Promoting Lifestyle among Dental Students in Zagreb, Croatia

Abstract: As future healthcare professionals, dental medicine students are expected to exhibit healthy lifestyle behaviors. This study aims to assess the health-promoting behaviors among undergraduate dental medicine students of all six academic study years at the University of Zagreb, and determine their predictors. Students were invited to complete a two-part survey, consisting of a self-reported sociodemographic questionnaire and the Health-Promoting Lifestyle Profile II (HPLP II). Three hundred and forty-nine studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…(20) As regards the relation between grades of HPLP score and field of study, the current study showed that there was a highly statistically significant difference between grades of HPLP II score of the studied students and their field of study. This in line with a study conducted by Lolokote , Alzahrani et al and Musić et al (21,30,31) . As regards relation between grades of HPLP and weight of the studied students, there was statistically significant difference between grades of HPLP score according to weight of the studied students.…”
Section: Discussionsupporting
confidence: 91%
“…(20) As regards the relation between grades of HPLP score and field of study, the current study showed that there was a highly statistically significant difference between grades of HPLP II score of the studied students and their field of study. This in line with a study conducted by Lolokote , Alzahrani et al and Musić et al (21,30,31) . As regards relation between grades of HPLP and weight of the studied students, there was statistically significant difference between grades of HPLP score according to weight of the studied students.…”
Section: Discussionsupporting
confidence: 91%
“…Moderate resistance to stress showed relatively increased effectiveness in increasing the level of awareness of healthy practices among students. Stress management training has been shown to be beneficial when the annual curriculum includes stress management education courses [ 5 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to facilitate the process of transforming intention into behavior, it must be supported both by increased self-efficacy and social support, since some daily behaviors (tooth brushing or flossing) do not depend on intention but on habits and social support. In most studies, physical activity had one of the lowest overall scores among the subcategories [ 5 , 34 , 35 ]. Between 40% and 50% of students seem to be sedentary and physically inactive [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation